(untitled) (قضايا سياسية, 2025)
Indeed, the international importance given to the Middle East region is due to a number of factors of strategic, political and economic nature, in addition to religious (ethnic) and civilizational importance. This region was and still is one of the most prominent regions in the world in terms of the multiplicity of entry points for control and acquisition by a not insignificant number of global and international poles, until the Middle East region became the main key that countries are trying hard to tighten their grip on. For example, the Turkish strategy towards this region was endowed with the elements of orientation towards it, especially after the (Justice and Development Party) took over the reins of power in 2002, and after the decline of its geostrategic position in the West, especially after its continuous stumbling regarding its accession to the European Union. Therefore, the change in the Turkish position towards the international and regional aspiration came accordingly. As for Iran's strategy towards the region, Iran has become a major and prominent role in the region, especially after the success of the Iranian revolution in 1979. With the imbalance in the Middle East, and the escalation of Turkish and Iranian interference in the region, due to their capabilities in all fields, especially the Iranian side, where the nuclear program appeared there, and the resulting conflicting international and regional positions. All of this has affected the intensity of the ongoing competition between these two countries. Of course, this competition has left effects and paths regarding the Turkish positions towards Iran's possession of this program. This is what our research will focus on in all its points.